2018
DOI: 10.5999/aps.2017.01431
|View full text |Cite
|
Sign up to set email alerts
|

Extension block and direct pinning methods for mallet fracture: A comparative study

Abstract: BackgroundMallet fracture can easily occur during sports activities or in daily life; however, the principles and methods of treatment for such fractures remain debated. Among the surgical treatments, various methods of closed reduction have been proposed. We treated patients with the extension block method (EBM) and the direct pinning method (DPM), and then compared the results. We assessed differences in range of motion and measurements of finger movement after surgery.MethodsA total of 41 patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Also, in the investigation of Han et al, 10 Our results were in agreement with study of Çapkın et al, 11 as they reported that no any complications were found, like the fracture fragmentation, nail deformation, volar subluxation, or dislocation or DIP joint osteoarthritis. 2-patients advanced surface infections, and one patient advanced skin necrosis; all of them were managed with oral anti-biotics and wound care, if required.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Also, in the investigation of Han et al, 10 Our results were in agreement with study of Çapkın et al, 11 as they reported that no any complications were found, like the fracture fragmentation, nail deformation, volar subluxation, or dislocation or DIP joint osteoarthritis. 2-patients advanced surface infections, and one patient advanced skin necrosis; all of them were managed with oral anti-biotics and wound care, if required.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, Han et al, 10 demonstrated that a number of 41-cases (29-men and 12-women) have involved in the current work, with ages mean of 36yrs (between, 15 and 62-yrs).…”
Section: Resultsmentioning
confidence: 81%
“…Additionally, very few studies in the literature have directly compared EBT with HPT; all of these comparative studies have small sample sizes. [ 18 , 27 , 29 ] A comparison of the longterm results of EBT with HPT would be a valuable contribution to the literature. Of note, all patients in the current study regained most of their functions at the end of the third month.…”
Section: Discussionmentioning
confidence: 99%
“…Yamanaka and Sasaki[ 30 ] used one or two compression pins to fix the dorsal fragment to the distal phalanx in 15 patients and obtained good results with 1 degree of hyperextension to 60 degrees of flexion. Also, Han et al[ 31 ] compared DBP and direct pinning and found that direct pinning was superior to DBP in terms of improvement in extensor lag and ROM; however, both groups achieved good results according to the Crawford criteria. In our practice, we prefer the direct pinning technique of Badia and Riano,[ 19 ] when the fragment size is close to 50% of the joint surface, since it provides straightforward reduction of the DIP joint.…”
Section: Discussionmentioning
confidence: 99%